(untitled) (BIBECHANA, 2020)
We present a study of spin vector orientation of 1218 SDSS (Sloan Digital Sky Survey) galaxies in Supercluster S [227+006+0078] having redshift 0.07 to 0.09. The database of these galaxies is taken from SDSS (Sloan Digital Sky Survey) 7th and 9th data release. We have converted two dimensional data to three dimensional by Godlowskian Transformation using position angle-inclination angle method. We intend to find non-random effects in the spatial orientation of galaxies in the Supercluster. No preferred alignment of angular momentum vectors is noticed, supporting Hierarchy model of galaxy formation. BIBECHANA 17 (2020) 117-122